A prospective self‐controlled study of topical timolol 0.5% cream for large superficial infantile hemangiomas. Issue 4 (6th February 2015) - Qiu, Yajing; Yang, Jingyan; Chen, Minyan; Chang, Lei; Wang, Tianyou; Ma, Gang; Jin, Yunbo; Chen, Hui; Lin, Xiaoxi
Abstract Timolol has recently been reported to be an effective and safe treatment for small and superficial infantile hemangiomas (IH). However, it is controversial to choose it as an alternative to oral propranolol for large superficial IH. In this study, we generated a new modified timolol agent as the base of an ointment. To evaluate the efficacy and safety of this new agent, we recruited 20 patients with large superficial IH. The average age was 4 months old. The average area of the IH was 28.8 cm2. The treatment was continued for 2–6 months. Three assessors were asked to judge the changes in both the treated and untreated parts separately by comparing photographs. After an average of 3.25 months of treatment, the average visual analog scale scores were 5.5 and 4.3 for those with and without the medication, respectively. The treated parts regressed significantly more than the untreated parts (P < 0.05). There were no side‐effects observed during treatment. High performance liquid chromatography was used to detect the serum concentration of timolol, and no timolol was detected in any of the blood samples (<0.02 μg/mL). Our new modified timolol agent is proven to be an effective therapy option for IH. Prospective studies with high‐precision serum timolol concentrations, with heart rate or blood pressure monitoring during treatment, are needed to evaluate potential systemic absorption when using timolol on large IH.